Moralność upolityczniona jako "usprawiedliwienie" różnych form przemocy. Etycy w obronie wartości zagrożonych = Political morality as a "justification" for various forms of violence - Dudek, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text deals with the place of ethics in social life and refers to the relationship between morality and politics. It is analyzed how all attempts to dominate the moral sphere by politics lead to the denial of the essence of morality, which is based on the agency of the subject, freedom of choices and responsibility for them, the intersubjective objectivity of judgments and norms, and the pursuit of universalization of values.
Keywords: moralność upolityczniona; przymus; przemoc; "swoi" i "obcy"; uzasadnienie; usprawiedliwienie; konflikt; politicized morality; coercion; violence; "own" and "foreign"; substantiation; justification; conflict